Influence of the substrate bias on the stoichiometry and structure of RF‐magnetron sputter‐deposited silver‐containing calcium phosphate coatings. Issue 2 (13th March 2013) - Ivanova, A. A.; Surmeneva, M. A.; Grubova, I. Y.; Sharonova, A. A.; Pichugin, V. F.; Chaikina, M. V.; Buck, V.; Prymak, O.; Epple, M.; Surmenev, R. A.
Abstract A coating on the basis of silver‐containing hydroxyapatite (silver‐hydroxyapatite) was deposited by radio frequency (RF) magnetron sputtering. X‐ray diffractometry, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and ellipsometry were used to analyse the change in structure and stoichiometry of the coatings upon the change of the negative electrical bias (–50 V and –100 V) on the substrate. The chemical composition of the sputter‐deposited coating was identical to the target. However, an increase in the negative electrical bias on the substrate led to a decrease of the coating thickness. In addition, the average size of the grains decreased from 55 ± 15 nm (grounded substrate) up to 30 ± 10 nm when an electrical bias of –100 V was applied.